The trend toward termination unit vocabulary Turkish. (Journal of Oriental Studies, 2016)
The article discusses the tendency to terminate vocabulary Turkish language, as well as to determine the features of this trend, its division into periods in connection with these features.
Keywords: terms; the period of Ataturk; Turkish terminology